Diseño de una máquina semi-automática de moler y moldear bolones de plátano para el cantón Quevedo provincia de Los Ríos, año 2015. - Egas García, Jeyson Patricio (2015)
Within the Ecuadorian market competitive, it is important for all industries hone their procedures so that you can get a production line with a much lower price. This project aims to provide a small company producing micro green boulders necessary tools to achieve this goal. With the use of sanitary materials, to design a machine that is capable of grinding banana cooked and process, with the final result in bolón banana perfectly conformed to this you try to automate the process so that minimal human involvement is required. For this the requirements requested by the customer for the design of the machine and the availability of materials readily available in the local environment is taken into account, since they are not machines of this type, which is designed here is considered a prototype so its cost will tend to be higher, however try to use easier and less expensive to obtain the final machine materials. It should be emphasized that this design may be subject to further improvement, ie correction of probable and defects that may occur during production that is not part of this project, this is mainly because as mentioned in the previous paragraph is a prototype and can contain design flaws.